معضلة أمن الطاقة: من الطاقات الأحفورية إلى الطاقات المتجددة - بقرار, ابوبكر (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تقدم هذه الورقة قراءة تحليلية لمعضلة الأمن الطاقوي،حيث يبدو تأثير التقيد بنمط إنتاج طاقوي تقليدي بدأت ملامح الترهل تظهر عليه محفوفا بالمخاطر، وبدأت تتعالي أصوات تزداد صخبا حول أهمية الاعتماد على موارد طاقوية صديقة للبيئة وتستجيب للتهديدات. انطلاقا من ذلك تهدف هذه الورقة العلمية إلى توضيح مدى قدرة النموذج الطاقوي المستجد على الإحلال مكان نموذج طاقوي ينظر إليه أنه ناضب، وفق مقاربة منهجية متقاطعة،و تتجلى أهمية هذه الدراسة في توضيح أهمية تعزيز أمن الطاقة من خلال تبني مخرجات أكثر استدامة تستجيب لتحديات و رهانات ذات أبعاد استراتيجية على المدى الطويل، و انتهت هذه الدراسة إلى مجموعة من النتائج أهمها أن حصة الطاقات المتجددة تنمو بشكل بطئ ولكن بثبات وترتبط أكثر بالمتغير التكنولوجي وكذا القضايا البيئية. This paper presents an analytical reading of the dilemma of the energy security, in which the effect of adhering to a traditional energy production pattern on which the features of sagging are beginning to be observed with risks, and increasingly vocal voices about the importance of relying on environmentally friendly energy resources that respond to threats. From this point of view, this scientific paper aims to clarify the new energy model's ability to replace an energy model that is perceived as depleted. The importance of this study is reflected in the importance of enhancing energy security by adopting more sustainable outputs that respond to challenges and stakes of strategic dimensions in the long term. The study concluded that the share of renewable energies is growing slowly but steadily and is more linked to technological change as well as environmental issues.